2018
DOI: 10.1186/s40644-018-0144-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound shear wave elastography of breast lesions: correlation of anisotropy with clinical and histopathological findings

Abstract: BackgroundUltrasound shear-wave elastography (SWE) may increase specificity of breast lesion assessment with ultrasound, but elasticity measurements may change with transducer orientation, defined as anisotropy. In this study, we aimed to observe the anisotropy of SWE of breast lesions, and its correlation with clinical and histopathological findings.MethodsThis retrospective study was approved by institutional review board. From June 2014 to June 2015, a total of 276 women (mean age, 48.75 ± 12.12 years) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Thirdly, only a single view plane has been utilized in this study. It has been shown in previous studies that anisotropy correlates with some prognostic factors in breast cancer [ 40 , 41 ]. Therefore, further prospective comparison studies with larger recruitments are necessary to compare the mean elasticity along the two orthogonal orientations of the shear waves.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, only a single view plane has been utilized in this study. It has been shown in previous studies that anisotropy correlates with some prognostic factors in breast cancer [ 40 , 41 ]. Therefore, further prospective comparison studies with larger recruitments are necessary to compare the mean elasticity along the two orthogonal orientations of the shear waves.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, ultrasound SWE has reported to detect differences between healthy and pathological tissues. [ 18 – 23 ] Although several studies explored the association between SWEP and CPC in patients with BC, no systematic review has undertaken this topic. This study will systematically and comprehensively investigate the association between SWEP and CPC in BC.…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported that ultrasound shear wave elastography (SWE) can supply novel insights into the shear elastic modulus of soft tissues. [ 18 – 23 ] It can be used to detect differences between healthy and pathological tissues. [ 18 – 23 ] It is reported that ultrasound SWE has used for the detection of patients with BC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DtP >15 mm on mammography and ultrasound implies that the lesion is probably malignant. 36 On the other hand, this feature has not been associated with malignancy for shear wave elastography, 37 and there is no literature available regarding DtP in CEUS. In the present study, DtP of malignant lesions (true positive and false negative) was larger than for benign lesions.…”
Section: Discussionmentioning
confidence: 99%